A combination of cognitive training and physical exercise for elderly with the mild cognitive impairment: A systematic review - Ida Untari; Achmad Arman Subijanto; Dyah Kurnia Mirawati; Ari Natalia Probandari; Rossi Sanusi (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The purpose of this paper is to conduct systematic reviews on Indonesian papers, to examine the most recent evidence of the efficacy of the combination of cognitive training and physical exercise, and to make recommendations in order to improve prevention, care and treatment services in elderly patients with mild cognitive impairment (MCI). Design/methodology/approach - The databases of Cochrane, Medline, NIH (US National Library Medicine), ProQuest, EbscoHost, Clinical Key, EMBASE, Medical Librarian (TWE) in Ovid, Science Direct, Scopus, The Lancet Global Health, PubMed, Emerald, Indonesian National Library, Google Scholar, Google Indonesia, and Garuda Portal were systematically searched using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to obtain empirical papers published between June 1976 and January 2018. Findings - Out of the 3,293 articles collected, 10 were included in this analysis. The result of this combined meta-analysis compares the combination therapy group (cognitive therapy and physical exercise) with a control group. It shows that the control group was likely to experience MCI 1.65 times more often than the combination therapy group. According to the result acquired from the synthesized meta-analysis, the control group experienced MCI 1.65 times higher than the combination therapy. The finding is proven to be statistically significant (95% CI= 1.42-1.93). Research limitations/implications - The research considers only English and Indonesian articles. Practical implications - It is important to explore the most effective training characteristics in a special combined intervention differentiated by the duration, frequency, intervention, type and combination mode. There is a need for further investigation that focuses on the physiological mechanisms underlying the positive effects, by inserting a more comprehensive neuro-imaging measurement to assess specifically the domain that benefits in terms of cognitive functions and molecular markers. Finally, exploratory studies are definitely required, which will specifically examine maintenance and treatment effects as well as derive theoretical explanations related to the interventions and predictors. Social implications - A combination of cognitive training and physical exercise intervention may improve the global health or cognitive functions. Originality/value - A combination of cognitive training and physical exercise has been found to improve prevention, care and treatment services in elderly patients with MCI. There is an increase in value in comparison to the study of Karssemeijer, which considered five Indonesian articles.